An analysis of the portrayal of the gender performance of Viola in Twelfth Night and She's the Man - SANTOS, Sofia Paez Lindoso dos (2023)
Cross-dressing in both media and real-life has been around for ages, but it has often been regarded as something shameful. In Shakespeare's Twelfth Night, the theme is approached differently as it is birthed out of the need to survive of its main character. This work intends to analyze both the play and its film adaptation She's the Man and point out similarities and differences between the main characters' motivations, how they, each in their own way, defy the patriarchal society they are inserted in, through their cross-dressing, and how the concepts of masculinity and femininity influence their gender performance. It proposes the use of critical thinking regarding these themes that, according to many, rarely occur nowadays, and how works can have the same root problems even being more than four centuries apart.